The Dynamics of the Term Structure of Interest Rates in the United States in Light of the Financial Crisis of 2007-10 - Rodriguez Waldo, Marco (IMF Working Papers; Working Paper, 2011)
This paper assesses the dynamics of the term structure of interest rates in the United States in light of the financial crisis in 2007-10. In particular, this paper assesses the dynamics of the term structure of U.S. Treasury security yields in light of economic and financial events and the monetary policy response since the inception of the crisis in mid-2007. To this end, this paper relies on estimates of the term structure using Nelson-Siegel models that make use of unobservable or latent factors and macroeconomic variables. The paper concludes that both the latent factors and macroeconomic variables explain the dynamics of the term structure of interest rates, and the expectations of the impact on macroeconomic variables of changes in financial factors, and vice versa, have changed little with the financial crisis.